Altered Interaction of the Matrix Protein with the Cytoplasmic Tail of Hemagglutinin Modulates Measles Virus Growth by Affecting Virus Assembly and Cell-Cell Fusion - Tahara, Maino (American Society for Microbiology, 2007)
Clinical isolates of measles virus (MV) use signaling lymphocyte activation molecule (SLAM) as a cellular receptor, whereas vaccine and laboratory strains may utilize the ubiquitously expressed CD46 as an additional receptor. MVs also infect, albeit inefficiently, SLAM(−) cells, via a SLAM- and CD46-independent pathway. Our previous study with recombinant chimeric viruses revealed that not only the receptor-binding hemagglutinin (H) but also the matrix (M) protein of the Edmonston vaccine strain can confer on an MV clinical isolate the ability to grow well in SLAM(−) Vero cells. Two substitutions (P64S and E89K) in the M protein which are present in many vaccine strains were found to be responsible for the efficient growth of recombinant virus in Vero cells. Here we show that the P64S and E89K substitutions allow a strong interaction of the M protein with the cytoplasmic tail of the H protein, thereby enhancing the assembly of infectious particles in Vero cells. These substitutions, however, are not necessarily advantageous for MVs, as they inhibit SLAM-dependent cell-cell fusion, thus reducing virus growth in SLAM(+) B-lymphoblastoid B95a cells. When the cytoplasmic tail of the H protein is deleted, a virus with an M protein possessing the P64S and E89K substitutions no longer grows well in Vero cells yet causes cell-cell fusion and replicates efficiently in B95a cells. These results reveal a novel mechanism of adaptation and attenuation of MV in which the altered interaction of the M protein with the cytoplasmic tail of the H protein modulates MV growth in different cell types.